Analysis of Household Consumers’ Preferences for Packaged Milk - Nugroho, Yudishtira Adhi; Mukson, Mukson; Mulyanto Setiawan, Bambang (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
Increasing national milk consumption is a big opportunity for milk producers. In meeting market demands, producers must consider consumers’ preferences. This research studied household characteristics, decision making processes, and preferences for packaged milk attributes in Jaten District. The study was conducted in December 2019 - January 2020 in Jaten District, Karanganyar. The research method used was survey method with 100 respondents from household consumers. Data collection was carried out by interview, observation and literature study. The data were implemented with descriptive analysis and conjoint analysis. The results showed that household respondents in Jaten District had the following characteristics: women (80%), ages 31-40 (36%), family size of 6 people (25%), high school education (36%), income of IDR 2,000. 000-2,5000 .000 / month (58%), milk purchasing costs IDR 10,000-25,000 / month (56%) with consumption of 3-4 packages / month (50%). Decision on the purchase of packaged milk consists of identifying needs, seeking information, evaluating alternatives, purchasing decisions, and post-purchase challenges. Household consumers’ preferences for packaged milk products are those with mocca flavor, with prices less than IDR 5,000 per package, well-known brand, box packaging, and have clear expiration information. Prioritized attributes are expiration date, price, taste, brand, and packaging. The results of this study can be used as a reference by producers to maximize packaged milk products based on existing attributes.